Testing Cluster Membership of Planetary Nebulae with High-precision Proper Motions. II. HST Observations of PHR J1315–6555 in the Open Cluster AL 1 (ESO 96-SC04) - Andrea Bellini; Howard E. Bond; Kailash C. Sahu (The Astronomical Journal)
Planetary nebulae (PNe) shown to be members of star clusters provide information on their properties and evolutionary histories that cannot be determined for PNe in the field, in particular the initial masses of their progenitor stars. Here we investigate the bipolar PN PHR J1315−6555 (hereafter PHR J1315), which lies near the open cluster AL 1 (ESO 96-SC04) on the sky. Previous work has established that the PN and cluster have similar radial velocities and amounts of interstellar reddening, and similar distances estimated using independent methods. We have obtained new images of the PN and cluster using the Hubble Space Telescope (HST). Combined with archival HST frames taken 12 yr earlier, they provide high-precision proper motions (PMs) for two candidate central stars of PHR J1315. We find that the PMs of both candidates are consistent with those of cluster members, strongly confirming the PN’s membership in AL 1. The candidate lying closer to the center of PHR J1315 has the color and luminosity of an early F-type dwarf, suggesting that it may be the optical primary in a close post-common-envelope binary. We used the HST data to construct a color–magnitude diagram for AL 1, which we corrected for significant foreground differential reddening. Isochrone fitting reveals that the cluster lies at a remarkably large distance of about 13 kpc, and has an age of about 1.0 Gyr. The initial mass of the progenitor of PHR J1315 was about 2.1 M _⊙ . We suggest follow-up investigations that would provide tighter constraints on the object’s evolution.